2013
DOI: 10.1002/ijc.28631
|View full text |Cite
|
Sign up to set email alerts
|

Oncolytic viral therapy with a combination of HF10, a herpes simplex virus type 1 variant and granulocyte–macrophage colony‐stimulating factor for murine ovarian cancer

Abstract: Ovarian cancer is the most frequent cause of gynecological cancer-related mortality as a majority of patients are diagnosed at an advanced stage with intraperitoneal dissemination because of the absence of initial symptoms. Granulocyte-macrophage colony-stimulating factor (GM-CSF) plays an important role in the maturation of specialized antigen-presenting cells. In this study, we utilized a herpes simplex virus (HSV) amplicon expressing murine GM-CSF combined with HF10 (mGM-CSF amplicon), a highly attenuated H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(26 citation statements)
references
References 43 publications
0
26
0
Order By: Relevance
“…Indeed, cell-based nanocarriers have been developed for not only cancer chemotherapy, but also a wide range of microbial infections (34)(35)(36). Macrophagebased nanomedicine delivery schemes may have several advantages over more conventional drug delivery, including enhanced cure rates, reduced side effects, increased drug stability, and effective subcellular targeting (26,27,37,38).…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, cell-based nanocarriers have been developed for not only cancer chemotherapy, but also a wide range of microbial infections (34)(35)(36). Macrophagebased nanomedicine delivery schemes may have several advantages over more conventional drug delivery, including enhanced cure rates, reduced side effects, increased drug stability, and effective subcellular targeting (26,27,37,38).…”
Section: Discussionmentioning
confidence: 99%
“…It has been demonstrated that many cytokines alone have some anti-tumor effect (e.g. GM-CSF, IL-12 and IL-2), and some recombinant cytokines have been developed into an adjuvant in tumor treatments [11,12]. Among these cytokines, GM-CSF is one of the better-studied molecules and has many roles in immune regulation.…”
Section: Functional Studies Of the Dna Vaccinementioning
confidence: 99%
“…The effects of HF10 have been studied in various types of malignant antitumors, including breast, pancreas, colon, and ovarian cancers 13,16,21,22. Since 2003, we have been carrying out Phase I clinical trials of HF10 against recurrent breast cancer and advanced head and neck cancer,23–25 and since 2005, we have been applying HF10 to the treatment of nonresectable pancreatic cancer 14,22.…”
Section: Discussionmentioning
confidence: 99%